2021
DOI: 10.1073/pnas.2107389118
|View full text |Cite
|
Sign up to set email alerts
|

Biased M1 muscarinic receptor mutant mice show accelerated progression of prion neurodegenerative disease

Abstract: There are currently no treatments that can slow the progression of neurodegenerative diseases, such as Alzheimer’s disease (AD). There is, however, a growing body of evidence that activation of the M1 muscarinic acetylcholine receptor (M1-receptor) can not only restore memory loss in AD patients but in preclinical animal models can also slow neurodegenerative disease progression. The generation of an effective medicine targeting the M1-receptor has however been severely hampered by associated cholinergic adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The hippocampal and cortical areas of the brain were isolated from E16 embryos and primary culture carried out as described ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…The hippocampal and cortical areas of the brain were isolated from E16 embryos and primary culture carried out as described ( 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a related study, Scarpa et al (Scarpa et al, 2021) analyzed knockin mice expressing a phosphorylation-deficient version of the M 1 muscarinic receptor. This mutant receptor couples normally to G q/11 but is deficient in β-arrestin recruitment (Bradley et al, 2020).…”
Section: Muscarinic Receptor-mediated Cognitive Improvements Interest...mentioning
confidence: 99%
“…This mutant receptor couples normally to G q/11 but is deficient in β-arrestin recruitment (Bradley et al, 2020). Interestingly, the authors found that mouse prion disease progresses more rapidly in the M 1 receptor mutant mice as compared to WT littermates (Scarpa et al, 2021). Mouse prion disease, a progressive terminal neurodegenerative disease, displays many of the hallmarks of human Alzheimer's disease (AD) (Mallucci et al, 2003).…”
Section: Muscarinic Receptor-mediated Cognitive Improvements Interest...mentioning
confidence: 99%
“…While in cancer the GPCR–β-arrestin signalosomes play a crucial role in promoting disease progression, in neurodegeneration they are beneficial by slowing down the development of misfolded proteins involved in neurodegenerative disorders. This is the case of the M1 muscarinic receptor and its ability to efficiently signal through β-arrestin [ 111 , 112 ]. Mutant mice with phosphorylation-deficient M1 receptors have more rapid and pronounced misfolded prion-mediated neurodegeneration progression than controls.…”
Section: β-Arrestin-mediated Gpcr Compartmentalizationmentioning
confidence: 99%